Optimalisasi Pengolahan Air Limbah Laundry Menggunakan Media Zeolit dan Karbon Aktif dalam Filter Kombinasi Dua Tabung Kompak: Optimalisasi Pengolahan Air Limbah Laundry menggunakan Media Zeolit dan Karbon Aktif dalam Filter Kombinasi Dua Tabung Kompak - Muhammad Bagas Grahandikha, Muhammad Bagas; Pradiko, Hary; Rochaeni, Anni (LPPM ITK, 2025)
Laundry wastewater is a source of environmental pollution that requires attention because it contains various compounds such as surfactants, suspended solids, and organic compounds that have the potential to damage the quality of groundwater and surface water. This study aims to optimize laundry wastewater treatment in a compact two-tube combination filter containing zeolite and activated carbon media. The filter treats artificial laundry wastewater made with three concentration variations. The variations tested were the flow rate and wastewater concentration. The results showed that the best removal efficiency occurred when the zeolite media was positioned in the inner tube with a downward flow direction, then flowed to the activated carbon media in the outer tube with a downward flow direction as well. The best removal efficiency was achieved at a medium flow rate (0.06 L/s and an initial concentration of COD of 143 mg/L, surfactant of 27.5 mg/L, and TSS of 117 mg/L) with a COD removal efficiency of 67%, surfactant of 64%, and TSS of 91%. Several parameters have met the quality standards stipulated in Yogyakarta Special Region Regulation No. 7 of 2016 concerning Wastewater Quality Standards. Therefore, a combination filter with two compact tubes using zeolite and activated carbon media could be a solution to improve environmental quality..